PERAN GURU PENDIDIKAN AGAMA ISLAM DALAMMENANAMKAN NILAI MULTIKULTURAL PADA SISWA - Resti Yulastri; Arrum Husaini Safitri; Bunga Apralia; Mursyidatul Hilmah; Selviana Safitri (Najah Bestari, 2026)
This study employed a descriptive qualitative approach to analyze the role of Islamic Religious Education teachers in instilling multicultural values in students. The research data were collected through interviews, observations, and documentation. The results showed that Islamic Religious Education teachers play roles as educators, mentors, motivators, and role models in fostering attitudes of tolerance, mutual respect, and appreciation for diversity within the school environment. The strategies applied include integrating multicultural values into the learning process, habituating tolerant behavior, and conducting social activities among students. Supporting factors include a conducive school environment and cooperation between teachers and parents, while inhibiting factors stem from social environmental influences and students’ limited understanding of the importance of tolerance.